THE IMPACT OF TRADE POLICY REFORM ON SOUTH AFRICAN - MALULEKA, SIPHO MICHAEL (My University, 2011)
Over the past 15 years, South African agriculture has undergone key reforms in trade liberalization and market deregulation. This structural transformation paved the way to enter global value chains and created space for increased private sector participation in the agricultural trade and marketing economy not previously possible. Trade policies form the main economic ingredients for the country to participate actively in the global economy, i.e. the general and specific elements of each nation’s trade policy interact directly or indirectly with those of other nations in all economic transactions across international borders. Trade policy reflects how the government values the importance of foreign trade within a complex environment with distinct differences in consumption and production patterns, culture and tradition and local socio-economic conditions. Issues that are important for this study are whether the type of trade policy reforms that have thus far been undertaken, with their emphasis on trade liberalization, provide more or less opportunity than before. The calculation of RCA (revealed comparative advantage) for the period from 1991 to 2008 shows that the competitiveness of agricultural exports have declined since 1990. There is a sharp decline in all agricultural products from 1990 to 2008, with maize dropping out of the top-ten agricultural exports by value since 2000. The decline could be attributed to the deregulation of marketing boards and increased global competition. The main recommendation from the study is that trade policy should in the future take into account domestic production capabilities or potentialities and the degree of trade and production distortions on these products at the global level
MM - P&DM
Keywords: Trade policy reforms; Agricultural exports; Agriculture